Visual Rehabilitation After Retinal Prosthesis Implantation: An 18-month Case Report, From Candidate Selection to Follow-Up. (March 2022) - Carignan, Mathieu; Courchesne, Marie; Cantin, Sylvie; Moore, Vincent; Poncet, Frédérique
Introduction: Various retinal implants are being developed and appear to be a promising option for improving the visual capacities of individuals with retinal dystrophy. A multidisciplinary approach to both assessment of a candidate's factors and rehabilitation could contribute to improved activity and participation. The purpose of this study was (i) to document the approach taken by a multidisciplinary team in the candidate selection process and in training in the use of the Argus II retinal prosthesis system (RPS), and (ii) to examine the effects of the RPS on sensory and mental functions and on activity and participation.Methods: An A1-B1-A2-B2 experimental case report was used, with repeated measures pre- and post-rehabilitation program design. The A phases represent the periods with the system off, whereas the B phases represent the periods with the system on. A 65-year-old man with retinitis pigmentosa and total blindness was followed by a multidisciplinary team for over 18 months. After receiving the retinal implant, he benefited from a 10-week rehabilitation program (twice per week; B1 phase).Results: Globally, the RPS improved vision in the B phases when the system was on and visual acuity was stable at 2.3 logMAR (functional blindness). The participant's mental and neuromusculoskeletal function scores were generally stable throughout the data collection periods. Lower performance on some measures at the end of phase B2 coincided with a negative mood.Discussion: Use of the RPS improved activity, but this did not transfer into greater participation in the living environment. Despite efforts made by the rehabilitation team to manage the user's expectations concerning the RPS, the interventions reactivated his grieving over his vision loss.Implications for Practitioners: New technologies can make users dream of unrealistic possibilities, and managing their expectations requires problem solving supported by a multidisciplinary team.